Phenotypic characterization of Lith genes that determine susceptibility to cholesterol cholelithiasis in inbred mice: physical-chemistry of gallbladder bile - D Q Wang; B Paigen; M C Carey (Journal of Lipid Research, 1997)
Lith genes control susceptibility to cholesterol gallstone formation in inbred strains of mice on a lithogenic diet containing high fat, high cholesterol and 0.5% cholic acid. Our study defines the physical-chemical phenotypes of C57L, AKR, and (C57L x AKR) F1 mouse gallbladder biles during 56 days on the lithogenic diet. We found enhanced cholesterol supersaturation, accumulation of mucin gel, and larger gallbladders in all C57L and F1 mice, as well as more frequent gallstone formation in male C57L and F1 mice (80%) compared to females (40%) or AKR mice (15%). In male C57L and F1 mice, mucin gel accumulated at 3 days, followed by cholesterol supersaturation and phase separation of liquid crystals, solid monohydrate crystals, and, in 43% of mice, anhydrous cholesterol crystals; whereas, in females, phase separations were delayed 2 to 9 days, and anhydrous crystals did not form. In AKR mice, cholesterol supersaturation and phase separations were infrequent and delayed, and gender did not influence the phenotype. Taurocholate invariably replaced endogenous bile salts, especially tauro-beta-muricholate, with crystallization sequences matching taurocholate-containing model bile systems. We conclude: i) Lith genes determine biliary cholesterol supersaturation, mucin gel accumulation, gallbladder size, phase-separation, and prevalence of cholesterol gallstones. ii) Identical phenotypes in C57L and F1 mice indicate susceptibility to cholesterol gallstones is genetically dominant, favoring males 2:1. iii) Mucin gel accumulation, crystallization, and stone formation are rare in AKR mice. This definition of the physical chemistry of lithogenesis should aid in further elucidation of the Lith genes and the proteins they encode.